2016
DOI: 10.1080/09638288.2016.1226415
|View full text |Cite
|
Sign up to set email alerts
|

What psychological and physical changes predict patients’ attainment of personally meaningful goals six months following a CBT based pain management intervention?

Abstract: The achievement of personally important goals was most significantly associated with change in walking ability and self-efficacy, while controlling for the influence of change in pain. Implications for Rehabilitation Chronic pain can reduce psychological and physical functioning, leading to a reduction in meaningful activities. Achievement of personally important activities as measured by Goal Attainment Scaling can be a more sensitive measure of programme outcome than that captured by many other standard meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Esto se corresponde con lo reflejado en otros estudios que encuentran resultados similares los nuestro (Denison, Åsenlöf, & Lindberg, 2004;Flink, Smeets, Bergbom, & Peters, 2015;Inoue et al, 2014;Oliver, Fisher, & Childs, 2016).…”
Section: Discussionunclassified
“…Esto se corresponde con lo reflejado en otros estudios que encuentran resultados similares los nuestro (Denison, Åsenlöf, & Lindberg, 2004;Flink, Smeets, Bergbom, & Peters, 2015;Inoue et al, 2014;Oliver, Fisher, & Childs, 2016).…”
Section: Discussionunclassified
“…Table 2 summarizes extracted data from the included articles. Identified studies were predominantly observational cohort studies that investigated the feasibility of GAS in clinical practice, 41,44 its validity and sensitivity, 37,45,52 and associations with measures of patient satisfaction 21,42 and standard outcome measures 21,[41][42][43][44] in patients with LBP. All studies investigated GAS as an outcome measure, while one study 45 also considered GAS as an intervention.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…All studies investigated GAS as an outcome measure, while one study 45 also considered GAS as an intervention. Physiotherapists 37,44 applied GAS in two of the seven included studies, while four studies indicated that GAS was applied by an unspecified provider 42,45 or "therapist," 41,52 and one was completed by an occupational therapist. 21 Those studies that did not specify the provider were composed of multidisciplinary teams that include physical therapy, occupational therapy, and/or psychology; therefore, the term "therapist" may be used to describe any of these providers.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Multidisciplinary pain management programmes aim to reduce the individual and socioeconomic burden of chronic pain, by developing coping skills based on positive changes in both cognitive and behavioural responses to pain (cognitive behavioural therapy; CBT). The ultimate goal of treatment is to promote self-management skills by maximising an individual’s physical, functional and psychological capacity, and in turn to develop their confidence to cope and participate in daily life despite the ongoing presence of pain (Edwards et al., 2016; Miró et al., 2018; Oliver et al., 2017). While the approach and content of treatment varies between pain management programmes, and it is difficult to define specific active ‘ingredients’ of treatment, these programmes have been found to be more effective than stand-alone therapies (Persson et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pain self-efficacy is positively associated with adjustment to a persistent pain condition (Jensen et al., 1991), enhanced activity engagement and lower disability (Martinez-Calderon et al., 2018; Oliver et al., 2017). However, the positive effects of pain self-efficacy require patients to develop and maintain the motivation to persist with behaviour change despite ongoing pain.…”
Section: Introductionmentioning
confidence: 99%